2005
DOI: 10.1002/pbc.20639
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic findings after 5‐HT3 receptor antagonists and chemotherapy in children with cancer

Abstract: Although we observed minor ECG changes after 5-HT3 receptor antagonists and chemotherapy, neither dangerous rhythm disturbances nor serious ECG changes were seen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Some evidence suggests that they prolong the QT interval on electrocardiography [17, 18], which is associated with an increased risk of serious ventricular arrhythmias (e.g., torsades de pointes). In vitro studies have indicated that 5-HT 3 receptor antagonists block voltage-dependent sodium channels and human ether-a-go-go-related gene potassium channels (cardiac ion channels), with the magnitude and type of electrocardiographic change depending on the particular drug.…”
Section: Introductionmentioning
confidence: 99%
“…Some evidence suggests that they prolong the QT interval on electrocardiography [17, 18], which is associated with an increased risk of serious ventricular arrhythmias (e.g., torsades de pointes). In vitro studies have indicated that 5-HT 3 receptor antagonists block voltage-dependent sodium channels and human ether-a-go-go-related gene potassium channels (cardiac ion channels), with the magnitude and type of electrocardiographic change depending on the particular drug.…”
Section: Introductionmentioning
confidence: 99%
“…Serotonin (5-HT 3 ) receptor antagonists reduce nausea and vomiting by inhibiting vagal nerves in the central nervous system and intestinal mucosa [3]. However, some evidence suggests that 5-HT 3 receptor antagonists can increase the risk of cardiac harm in children undergoing chemotherapy [4, 5]. Adverse events associated with these medications include a decrease in heart rate and prolongation of the QT interval.…”
Section: Introductionmentioning
confidence: 99%
“…In the second study, a similar transient increase in the QT interval was observed, but was not found to be clinically significant [11]. In this study, the prolonged QT interval was associated with the 5-HT3 receptor antagonist granisetron but not with ondansetron [11]. The relationship between 5-HT3 receptor antagonists and cardiac risk has not been confirmed by systematic review.…”
Section: Introductionmentioning
confidence: 64%
“…In the first study, the QT interval was increased up to 24 hours after the antiemetic was given, but this was asymptomatic and serious arrhythmias were not noted [10]. In the second study, a similar transient increase in the QT interval was observed, but was not found to be clinically significant [11]. In this study, the prolonged QT interval was associated with the 5-HT3 receptor antagonist granisetron but not with ondansetron [11].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation